The Role of Anthroponymic Commemoration on Wine Labels in South Africa. (3rd April 2017) - Neethling, Bertie
Abstract : South Africa is a prominent wine-producing country. The focus in this contribution will be on anthroponymic commemoration whereby a name of a person, singular or plural, and of both genders, is selected for a particular wine in South Africa. This selection is often linked to historical figures, but also sometimes uses invented or fictional names. Others may simply commemorate the winemaker, or family members. Being a multilingual country the language choice also will be discussed. The contribution therefore will outline the various categories and the possible impact of the name as well as the design of the label, the description of the name, and the language used for the description.